Making sense of social involvement with disadvantaged apprentices : narrative patterns of actors in a profit-oriented company - Bahl, Anke [Verfasser] (My University, 2023)
"This chapter looks at morality as an organizational practice in the context of vocational training provided by a !arge German industrial company. Company A is a long-time player in a social training initiative of local firms and civic stakeholders. One aim is to prevent unemployment of young people in the region by offering additional apprenticeship placements. By pooling the resources of its members, the initiative can offer apprenticeship schemes in partnerships of up to eight changing companies. Tue program is aimed exclusively at candidates with placement barriers who have previously not been able to find a training place. Company A offers training sections of three to six months to them, and it does so in addition to its own apprenticeship programs. This practice provides some challenges since the dominant logic at work in the productive sector is a profit-oriented one. Tue argument made by two managers representing the training and a technical department of company A will be examined as examples. How do they explain and legitimize their involvement in this social initiative given their economically driven work environment? Furthermore, how do they defend their decision to drop and reject certain participants who do not show the expected behaviour and "seize the opportunity" so generously provided to them? Tue theoretical framework of the Economics and Sociology of Conventions (ECISC) (Diaz-Bone, 2011, 2018; Diaz-Bone & Larquier, 2022) with its different worlds of social coordination will be tested for its applicability. Before looking at the narrative patterns of two interviews in detail, some preliminary remarks on the general context of initial in-company training in Germany and on the background to this case are necessary. Furthermore, the empirical situation of the field visit will be introduced." (Authors' abstract, BIBB-Doku)
Keywords: P 1.7 Benachteiligte; S 1.3 Berufliche Erstausbildung; 370; Benachteiligter Jugendlicher; Ausbildungsplatzförderung; Ausbildungsverbund; Industriebetrieb; Soziales Handeln